Introgressing cry1Ac for Pod Borer Resistance in Chickpea Through Marker-Assisted Backcross Breeding - Kaur, Ajinder; Sharma, Urvashi; Singh, Sarvjeet; Singh, Ravinder; Vikal, Yogesh; Singh, Satnam; Malik, Palvi; Kaur, Khushpreet; Singh, Inderjit; Bindra, Shayla; Sarmah, Bidyut Kumar; Sandhu, Jagdeep Singh (Frontiers in Genetics, 2022)
Gram pod borer, Helicoverpa armigera is a major constraint to chickpea (Cicer arietinum L.) production worldwide reducing crop yield by upto 90%. The constraint is difficult to overcome as chickpea germplasm including wild species either lack pod borer resistance, or if possessing resistance are cross-incompatible. This study describes conversion of elite, but pod borer susceptible commercial chickpea cultivars into resistant through introgression of cry1Ac using marker assisted backcross breeding. The chickpea cultivars (PBG7, L552) were crossed with pod borer resistant transgenic lines (BS 100B, BS 100E) carrying cry1Ac that led to development of BC1F1, BC1F2, BC1F3, BC2F1, BC2F2, BC2F3 populations from three cross combinations. The foreground selection revealed that 35.38% BC1F1, 8.4% BC1F2 plants obtained from Cross A (PBG7 x BS 100B); 50% BC1F1, 76.5 % BC1F2 plants from Cross B (L552 x BS 100E); 12.05% BC2F2 and 82.81% (average) BC2F3 plants derived from Cross C (PBG7 x BS 100E) carried cry1Ac gene. The bioassay of backcross populations for toxicity to H. armigera displayed up to 100% larval mortality. BC1F1, BC1F2 populations derived from Cross B and BC2F3 population from Cross C segregated in Mendelian ratio for cry1Ac confirming inheritance of single copy of transgene, whereas BC1F1, BC1F2 populations obtained from Cross A and BC2F2 population from Cross C exhibited distorted segregation ratios. BC1F1 plants of Cross A and Cross B accumulated Cry1Ac protein ranging from 11.03 to 11.71 µgg-1 leaf tissue. cry1Ac positive BC2F2 plants from Cross C demonstrated high recurrent parent genome recovery (91.3%) through background selection using SSR markers and phenome recovery of 90.94%, amongst these 30% plants were homozygous for transgene. The performance of BC2F3 progenies derived from homozygous plants was similar to recurrent parent for main agronomic traits, such as number of pods and seed yield per plant. These progenies are valuable source for H. armigera resistance in chickpea breeding programs.